Dustproof pellicle assembly and method of manufacturing same
Through the annealing treatment of the dust -proof film, the problem of decreased and vibration of the film is solved, the position accuracy of the pattern in the photocal step is improved, and the higher optical precision accuracy is achieved.
Patent Information
- Application Number
- CN202411386062.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-03
- Filing Date
- 2019-11-27
- Publication Date
- 2025-01-21
AI Technical Summary
In the lithography step, the filmization of the dust-proof film leads to a decrease in intensity, resulting in high-speed scanning motion during exposure causing film vibration, which in turn leads to dissipation of exposure light and deterioration of pattern position accuracy.
By annealing the dust-proof film, its strength is increased and film vibration caused by high-speed scanning motion is alleviated, thereby suppressing the deterioration of pattern position accuracy.
By improving the intensity of the dust -proof film, reduce the vibration, ensure the stability of the exposure light, improve the position accuracy of the transfer of the pattern, and effectively use it for the formation of a fine pattern.
Smart Images

Figure BDA0005070999110000091
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with the application date of November 27, 2019, application number CN201911183115.8, and invention name “Dust-proof film assembly and its manufacturing method”. Technical Field
[0002] The invention relates to a dustproof film frame and a dustproof film assembly for photolithography formed by using the dustproof film frame. Background Art
[0003] In the photolithography step when manufacturing semiconductor devices or liquid crystal displays, a semiconductor wafer coated with photoresist or a liquid crystal original plate is irradiated with light to form a pattern. However, if the photomask or shrink photomask (hereinafter referred to as a photomask) used at this time is contaminated with foreign matter, the foreign matter will absorb the light or cause the light to bend, so that the transferred pattern will be deformed, the edges will become rough, and the base may even have black dirt, resulting in problems such as damage to size, quality, and appearance.
[0004] These photolithography steps are usually carried out in a clean room, but even so it is difficult to keep the exposure original plate clean all the time, so a method is generally adopted to set a foreign body blocker called a dustproof film assembly on the exposure original plate before exposure.
[0005] Such a pellicle assembly is generally composed of a frame-shaped pellicle frame, a pellicle stretched on the upper end surface of the pellicle frame, and an airtight gasket formed on the lower end surface of the pellicle frame. The pellicle is made of a material with a high transmittance to the exposure light, and an adhesive is used as the airtight gasket.
[0006] If such a pellicle is set on the photomask, foreign matter will not adhere directly to the photomask but to the pellicle. Then, as long as the focus is on the pattern on the photomask during photolithography, foreign matter on the pellicle will not affect the transfer, and problems such as pattern deformation can be suppressed.
[0007] In this type of photolithography, as a method to improve resolution, the exposure light source is being promoted to a shorter wavelength. Until now, the exposure light source has evolved from the g-line (436nm) and i-line (365nm) generated by a mercury lamp to the krypton fluoride excimer laser (248nm); and in recent years, when micro-processing is required, the most commonly used is the argon fluoride excimer laser (193nm).
[0008] In recent years, in order to use argon fluoride excimer lasers for more minute processing, liquid immersion exposure devices are used. By filling the space between the objective lens of the exposure device and the silicon wafer with liquid, a higher numerical aperture (NA) is achieved, resulting in a higher resolution. If the numerical aperture of the exposure device is increased in this way, the oblique incident angle of the peripheral part of the light penetrating the pellicle assembly will increase. The transmittance of the pellicle assembly is generally set to obtain a maximum transmittance for vertical incident light; however, a phenomenon has been observed that the transmittance decreases as the incident angle increases. The degree of this decrease in transmittance is more significant when the film thickness is thick. Therefore, in order to obtain a high transmittance even for oblique incident light, the pellicle is generally made thinner.
[0009] However, once the dustproof film is made thinner, the problem of reduced film strength will follow. During exposure, the photomask unit made by sticking the dustproof film assembly on the photomask substrate will perform high-speed scanning motion. Therefore, when the dustproof film has a low strength, the film is prone to vibrate during the high-speed scanning motion. In other words, it is known that due to the vibration of the film, the exposure light is easily scattered when passing through the dustproof film, which may cause the pattern to deviate from the original target position and deteriorate the position accuracy (overlay) of the pattern.
[0010] In addition, as known technologies related to the process of improving the overlay, the following patent publications can be listed.
[0011]
Known technical literature
[0012] [Patent Literature]
[0013] [Patent Document 1] Japanese Patent Application Publication No. 2018-508048
[0014] [Patent Document 2] Japanese Patent No. 5821100 Summary of the invention
[0015] Problem that the invention aims to solve
[0016] In view of this, the present invention is developed to solve the above-mentioned problems, and its purpose is to provide a dustproof film assembly, which can improve the strength of the dustproof film, alleviate the vibration of the dustproof film caused by the high-speed scanning movement during exposure, and suppress the deterioration of overlay.
[0017] Solutions for solving problems
[0018] The inventor of this case has studied the above-mentioned subject carefully and found that by heating the dustproof film (annealing treatment), the strength of the dustproof film is improved compared with the case where the dustproof film is not subjected to such treatment. As a result, it is found that even in the high-speed scanning motion during exposure, the excessive vibration of the dustproof film can be alleviated; therefore, the exposure light will not be scattered when passing through the dustproof film, and the pattern can be transferred to the target position, and the deterioration of overlay after exposure can be suppressed, thereby achieving the present invention.
[0019] Therefore, the present invention provides the following pellicle and method for manufacturing the same.
[0020] 1. A dustproof film assembly, wherein a dustproof film is stretched on a dustproof film frame; the dustproof film is an annealed dustproof film.
[0021] 2. The pellicle assembly as described in item 1 above, wherein the film tension (film vibration frequency) of the pellicle stretched on the pellicle frame is greater than or equal to 30 Hz.
[0022] 3. A method for manufacturing a dustproof film assembly, which is a method for manufacturing a dustproof film assembly by stretching a dustproof film on a dustproof film frame; the method comprises one of the following steps: a step of annealing the dustproof film monomer before stretching the dustproof film on the dustproof film frame; a step of annealing the dustproof film assembly after the dustproof film is stretched; or a step of annealing the dustproof film monomer and the dustproof film assembly both before and after the dustproof film is stretched.
[0023] Effects of the Invention
[0024] Compared with the known dustproof film assembly, the dustproof film assembly of the present invention can improve the strength of the dustproof film due to the annealing treatment, and alleviate the vibration of the dustproof film caused by the high-speed scanning movement during exposure; therefore, the exposure light will not be scattered when passing through the dustproof film, and the pattern can be transferred to the target position, and the deterioration of overlay after exposure can be suppressed, which can be effectively used in the formation step of fine patterns. DETAILED DESCRIPTION
[0025] An embodiment of the present invention will be described in detail below, but the present invention is not limited thereto.
[0026] The pellicle of the present invention is particularly effective when used in semiconductor manufacturing where deformation of the photomask is particularly problematic, but is not limited to such applications. For example, it can be used not only in semiconductor manufacturing with a side of about 150 mm, but also in the manufacturing of printed circuit boards with a side of 200 to 300 mm, and in the manufacturing of liquid crystal and organic EL displays with a side of approximately 500 to 2000 mm. It can be used in all pellicles that may cause problems due to deformation of the photomask caused by the attachment of the pellicle.
[0027] Although not specifically shown in the figure, the pellicle assembly of the present invention comprises a frame-shaped pellicle frame and a pellicle film stretched on the upper end surface of the pellicle frame. As the material of the pellicle frame, metals or alloys such as aluminum alloy, steel, stainless steel, brass, invar, super invar, etc., engineering plastics such as PE (polyethylene), PA (polyamide), PEEK (polyether ether ketone), fiber composite materials such as GFRP (glass fiber reinforced plastic), CFRP (carbon fiber reinforced plastic), etc., and other well-known materials can be used.
[0028] Furthermore, it is preferred to perform a treatment to turn the surface black, and at the same time, if necessary, perform a surface treatment such as a coating to prevent dust generation. For example, in the case of using an aluminum alloy, it is preferred to perform a surface treatment such as anodizing aluminum treatment or chemical conversion treatment; and in the case of steel, stainless steel, etc., it is preferred to perform a surface treatment such as electroplating black chrome.
[0029] In order to capture or fix suspended foreign matter on the inner surface of the pellicle frame, it is preferred to apply an adhesive substance such as an acrylic adhesive or a silicone adhesive. Furthermore, in order to prevent dust generation, it is preferred to form a non-adhesive resin coating such as an acrylic resin or a fluorine resin only on the inner surface of the pellicle frame or on the entire surface. Such adhesive resin or non-adhesive resin coating can be formed by known methods such as spraying, dipping, powder coating, and electrodeposition coating.
[0030] Furthermore, a plurality of tooling holes or grooves may be provided at multiple locations on the outer surface of the dustproof film frame for the purpose of transportation, etc. Furthermore, it is preferred to mark the model, serial number or barcode, etc. by mechanical imprinting or laser engraving.
[0031] Furthermore, the dustproof film assembly of the present invention may also be provided with vents to adjust the internal air pressure, and a filter made of a porous film such as PTFE (polytetrafluoroethylene) may be installed to prevent foreign matter from invading the outside. In this case, the filter may be installed by directly attaching an adhesive layer of a suitable material to the outer surface of the dustproof film frame. Then, the configuration position or number of these vents or filters, and their shapes may be appropriately determined in consideration of the required air permeability or handling requirements.
[0032] The dustproof film used in the present invention can also be selected from the most suitable materials such as cellulose resin and fluorine resin according to the exposure light source used; and then the most suitable film thickness can be selected from the range of about 0.1 to 10 μm based on the viewpoints of transmittance, mechanical strength, etc.; and a reflection prevention layer can be added as needed. In particular, when EUV light (extreme ultraviolet light) is used as the exposure light source, an extremely thin silicon film or graphene film with a film thickness of less than 1 μm can be used. Then, the adhesive used to stretch the dustproof film on the upper end surface of the dustproof film frame can use a known adhesive such as an acrylic adhesive, a fluorine adhesive, a silicone adhesive, etc.
[0033] The adhesive layer used to mount the dustproof film assembly of the present invention to the photomask is provided on the lower end surface of the dustproof film frame. As the material of the adhesive layer, known materials such as rubber adhesive, urethane adhesive, acrylic adhesive, polystyrene-polyethylene-polybutylene-polystyrene (SEBS) adhesive, styrene-ethylene / propylene-styrene copolymer (SEPS) adhesive, silicone adhesive, etc. can be used. Furthermore, it is preferred to use a material that is less likely to release gas, which is the cause of turbidity.
[0034] In order to ensure the stability of the pellicle assembly after being mounted on the photomask or to reduce the impact on the photomask, it is preferred that the flatness of the adhesive layer surface is less than 30 μm. Furthermore, the cross-sectional shape or thickness can be selected as needed, for example, the cross-sectional shape can be a semicircular convex shape.
[0035] On the surface of the adhesive layer, a release film may be provided, which is about 50 to 300 μm thick and has a peeling property on the surface of a PET (polyethylene terephthalate) film, etc. This is a material used to protect the adhesive layer, and it may be omitted by ingenuity in the outer box of the dustproof film assembly or the support method of the dustproof film assembly.
[0036] In the present invention, by annealing the dustproof film unit before stretching the dustproof film frame, or by annealing the dustproof film assembly with the dustproof film stretched after the dustproof film is stretched, or by annealing the dustproof film unit and the dustproof film assembly both before and after stretching the dustproof film, the strength of the dustproof film can be improved compared to the case where no such treatment is performed, and the deterioration of the overlapping can be effectively suppressed.
[0037] The set temperature of the above annealing treatment (heating treatment) depends on the glass transition temperature (Tg) of the dustproof film (material) used. Generally, most dustproof films are amorphous. At a temperature above the glass transition temperature (Tg), wrinkles, breakage and other adverse effects will occur in the film, and it is expected that the tension will be reduced. Therefore, the optimal temperature for the annealing treatment is preferably Tg-5 to -50°C of the dustproof film material used, and more preferably -10 to -30°C. However, if the annealing temperature does not exceed the above Tg, it is expected that the tension will not be reduced, so it is expected that there will be no major problems in quality even if it is lower than the above. As for the set time of the above annealing treatment (heating treatment), it is preferably 1 to 48 hours, and more preferably 1 to 24 hours. If it is longer than the above set time, the film tension will hardly change, but the operating efficiency may be reduced. In addition, as for the above annealing treatment device, commercially available products can be used, for example, a machine made by Yamato Scientific Co., Ltd., the product name of which is "Clean Oven DE610U".
[0038] Furthermore, in the present invention, the film tension (film vibration frequency) of the dustproof film stretched on the dustproof film frame is preferably 30 Hz or more. If the film tension of the dustproof film is less than 30 Hz, the overlap will be greater than 1 nm, and the pattern position accuracy will deteriorate. The vibration frequency of the dustproof film can be measured, for example, by "PERSONAL FFT ANALYZER: CF-4210Z" manufactured by ONO SOKKI MEASUREMENT TECHNOLOGY CO., LTD.
[0039] In the present invention, a photomask unit made by attaching a pellicle assembly to a photomask substrate is patterned under high-speed scanning motion, and the overlay accuracy can be evaluated based on the misalignment from the target position toward the X direction and the Y direction. The smaller the misalignment in both directions, the better. For the next generation of semiconductor devices or liquid crystal displays, extremely fine pattern formation is required, and the overlay position accuracy is preferably below 1nm. Regarding the measurement of the misalignment from the patterned target position toward the X direction and the Y direction, for example, the wafer measurement machine "YIELDSTART-250D" manufactured by ASML Technology Co., Ltd. can be used for measurement.
[0040] [Example]
[0041] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0042] [Example 1]
[0043] In Example 1, first, an aluminum alloy pellicle frame (outer dimensions: 149 mm×115 mm×3.15 mm) was prepared, and a filter hole with a diameter of 10 mm was provided in the center of the short side of the pellicle frame.
[0044] Next, after the prepared pellicle frame was cleaned with pure water, CYTOP adhesive (trade name: CTX-A) manufactured by Asahi Glass Co., Ltd. was applied to the upper end surface of the pellicle frame, and acrylic adhesive (SK-Dyne 1495S manufactured by Soken Chemical Co., Ltd.) was applied to the lower end surface. After that, the pellicle frame was heated to 130°C to harden the adhesive and the glue.
[0045] Next, the adhesive layer side of the pellicle frame is attached to the 0.28μm thick pellicle made of CYTOP (trade name: CTX-S) manufactured by Asahi Glass Co., Ltd., which is attached to an aluminum frame larger than the pellicle frame, and the pellicle assembly is completed by removing the portion outside the pellicle frame. The Tg of CYTOP (trade name: CTX-S) manufactured by Asahi Glass Co., Ltd. is 108°C.
[0046] The manufactured dustproof film assembly was subjected to annealing treatment so that the vibration frequency of the dustproof film became 26 Hz. Specifically, the annealing treatment was performed at a set temperature of 50°C and a treatment time of 1 hour. Here, the vibration frequency of the dustproof film was measured using PERSONAL FFT ANALYZER: CF-4210Z manufactured by Ono Sokki Measurement Technology Co., Ltd. As a measurement method, a fixed impact was applied to the dustproof film assembly to vibrate the dustproof film, and then the vibration frequency was measured using a general noise meter manufactured by Ono Sokki Measurement Technology Co., Ltd., and the value displayed on PERSONAL FFT ANALYZER: CF-4210Z was used as the vibration frequency of the film. After measuring the film vibration frequency of this dustproof film, the dustproof film assembly was attached to a 150 mm square photomask substrate, and the overlay accuracy was evaluated. The overlay was 1.34 nm. In addition, the conditions for attaching the dustproof film assembly to the photomask were set to a load of 5 kgf and a load time of 30 seconds.
[0047] [Example 2]
[0048] In Example 2, a pellicle was produced in the same manner as in Example 1 except that the annealing treatment was performed at a set temperature of 70° C. and a treatment time of 1 hour so that the film vibration frequency of the pellicle became 28 Hz. At this time, the overlap was 1.07 nm.
[0049] [Example 3]
[0050] In Example 3, a pellicle was produced in the same manner as in Example 1 except that the annealing treatment was performed at a set temperature of 90° C. and a treatment time of 1 hour so that the film vibration frequency of the pellicle became 30 Hz. At this time, the overlap was 0.81 nm.
[0051] [Example 4]
[0052] In Example 4, a pellicle was produced in the same manner as in Example 1 except that the annealing treatment was performed at a set temperature of 90° C. and a treatment time of 12 hours so that the film vibration frequency of the pellicle became 32 Hz. At this time, the overlap was 0.51 nm.
[0053] [Example 5]
[0054] In Example 5, a pellicle was produced in the same manner as in Example 1 except that the annealing treatment was performed at a set temperature of 90° C. and a treatment time of 48 hours so that the film vibration frequency of the pellicle became 33 Hz. At this time, the overlap was 0.50 nm.
[0055] [Comparative Example 1]
[0056] Comparative Example 1 is a case where the pellicle is not subjected to annealing. The pellicle was produced in the same manner as in Example 1 except that the pellicle was not subjected to annealing. At this time, the pellicle vibration frequency of the pellicle was 24 Hz and the overlap was 1.54 nm.
[0057] [Comparative Example 2]
[0058] Comparative Example 2 is a case where the annealing temperature is set at 108°C. A pellicle assembly is produced in the same manner as in Example 1 except that the annealing temperature is set at 108°C and the annealing time is 1 hour. At this time, the pellicle vibration frequency of the pellicle is 15 Hz and the overlap is 2.83 nm.
[0059]
Table 1
[0060]
Claims
1. A method for manufacturing a pellicle assembly, the pellicle assembly being used in a liquid immersion exposure device using an argon fluoride excimer laser, the pellicle assembly having a pellicle stretched on a pellicle frame, the method for manufacturing the pellicle assembly being characterized by: The dustproof film is subjected to an annealing treatment at a temperature ranging from a glass transition temperature of the dustproof film -30°C to a glass transition temperature of the dustproof film -10°C.
2. The method for manufacturing a dustproof film assembly according to claim 1, wherein The dust-proof film has a thickness that can suppress a decrease in transmittance due to oblique incidence of light that passes through the dust-proof film.
3. The method for manufacturing a dustproof film assembly according to claim 1 or 2, wherein In the state in which the pellicle frame is stretched, the pellicle tension (membrane vibration frequency) of the pellicle is 30 to 33 Hz.
4. The method for manufacturing a dustproof film assembly according to claim 1 or 2, wherein The set time of the annealing treatment is 1 to 48 hours.
5. The method for manufacturing a dustproof film assembly according to claim 1 or 2, wherein The dustproof film is a film of fluorine-based resin.
6. A method for manufacturing a photomask having a pellicle assembly, characterized by: A step of preparing a pellicle manufactured by the pellicle manufacturing method according to any one of claims 1 to 5; and The step of attaching the pellicle assembly to a photomask.
7. An exposure method, characterized by: A step of preparing a pellicle manufactured by the pellicle manufacturing method according to any one of claims 1 to 5; and The step of performing exposure using the pellicle assembly.
8. A method for manufacturing a semiconductor device, characterized by comprising: A step of preparing a pellicle manufactured by the pellicle manufacturing method according to any one of claims 1 to 5; and The step of performing exposure using the pellicle assembly.
9. A method for manufacturing a liquid crystal display, characterized by comprising: A step of preparing a pellicle manufactured by the pellicle manufacturing method according to any one of claims 1 to 5; and The step of performing exposure using the pellicle assembly.
10. A method for manufacturing an organic EL display, characterized by comprising: A step of preparing a pellicle manufactured by the pellicle manufacturing method according to any one of claims 1 to 5; and The step of performing exposure using the pellicle assembly.
Citation Information
Patent Citations
Low temperature underground tank
JP1983021100A
Indirect surface cleaning apparatus and method
JP2018508048A